y = 12 or -1
2007-03-31 06:51:37
·
answer #1
·
answered by nemlo23 2
·
0⤊
0⤋
Basically you have to factor by reversing foil I've pasted a link below to explain:
y^2 + 13y + 12 = (y+12) (y+1) so y = -12 and y = -1,
2007-03-31 06:50:45
·
answer #2
·
answered by Dennis 1
·
0⤊
0⤋
This is a quadratic formula type of problem. x = [ -b ± sqrt(b^2 - 4ac) ] / 2a
Therefore, let's work this step-by-step.
First let's break the quadratic formula in two steps to be easier for you to understand.
Let's say that @ = b^2 - 4(a)(c)
@ = 13^2 - 4(1)(12)
@ = 169 - 4(12)
@ = 169 -48
@ = 121
Then we do Y = (-b ± square root of @) / 2a
Y = (-13 ± square root of 121) / 2 (1)
Y = (-13 ± 11) / 2
then do Y' = (-13 + 11)/2 = -1
and Y" = (-13 - 11) / 2 = -12
To double check if the answers are correct, insert each one of the Y values that we found in the equation [ y(square) + 13y + 12 ] and see if it is equal to zero.
2007-03-31 07:08:57
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
12 or -1
2007-03-31 06:46:41
·
answer #4
·
answered by Bronka 1
·
0⤊
0⤋
(y+1)(y+12)
y=-1 ;-12
2007-03-31 07:34:34
·
answer #5
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
y^2+13y+12=0
(y+12)(y+1)=0
y=12=0, so y= -12
y+1=0,so y= -1
2007-03-31 06:50:30
·
answer #6
·
answered by mc 3
·
0⤊
0⤋
13y+12=25yy(square)
2007-03-31 07:44:10
·
answer #7
·
answered by fennt 1
·
0⤊
0⤋
Use equation:
y(1or2)= -p/2 +or- second root from p(square)/4 -q
where the p is number at y and q is decimal number (in your case is 12). You'll get two solutions (y1 or y2) and therefore you got +or- in equation. Best Regards and veradisca! Neven
2007-03-31 06:54:48
·
answer #8
·
answered by NEVEN , 4
·
0⤊
0⤋
this implies...
(y+12)(y+1).
if it is equated to 0,y=-12,-1
2007-03-31 06:59:02
·
answer #9
·
answered by Anonymous
·
0⤊
0⤋
(y+12)(y+1) that was kinda easy
2007-03-31 06:48:58
·
answer #10
·
answered by Big Daddy 3
·
0⤊
0⤋